PROBLEMS IN THE IMPLEMENTATION OF ERP TECHNOLOGIES IN UZBEK MANUFACTURING ENTERPRISES AND WAYS TO SOLVE THEM - Raximjonov Orifjon Olimjon o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This study scientifically investigates the problems that arise during the implementation of ERP (Enterprise Resource Planning) technologies in manufacturing enterprises in Uzbekistan and ways to overcome them. By integrating ERP systems into the manufacturing sector, it is possible to achieve efficient use of resources by enterprises, digitization of production processes, and increased operational efficiency. At the same time, it was revealed that there are a number of obstacles related to technical, financial, organizational, and human resources in the process of implementing ERP systems in Uzbek enterprises. This article deeply studies the causes of these problems and offers effective solutions based on international experience. The results of the study are of practical importance for enterprise managers and policymakers.